3D Numerical Simulation Analysis of Passive Drag near Free Surface in Swimming - 詹杰民 李天赠 陈学彬 李毓湘 韦永康 (China ocean engineering, 2015)
The aim of this work is to build a 3D numerical model to study the characteristics of passive drag on competitive swimmers taking into account the impact of the free surface. This model solves the 3D incompressible Navier-Stokes equations using RNG k-ε turbulence closure. The volume of fluid（VOF） method is used to locate the free surface. The 3D virtual model is created by Computer Aided Industrial Design（CAID） software, Rhinoceros. Firstly, a specific posture of swimming is studied. The simulation results are in good agreement with the data from mannequin towing experiments. The effects of a swimmer＇s arms and legs positions on swimming performance are then studied. Finally, it is demonstrated that the present method is capable of simulating gliding near the free surface.